Penggunaan Media Sosial sebagai Sarana Pembelajaran Pendidikan Agama Islam di Era Digital - Ofki Meilola Malika; Rafika Dwi Prahesti; Zamzam Mustofa; Mukhlas Habibi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Social media is evidence of the advancement of the most recent technical innovations, which are an inextricable part of daily life. Young pupils are surely familiar with social media since they use internet technologies. In this scenario, using social media to obtain any information they want will be simpler. Thus, it is possible to construct learning that is both effective and efficient when using social media as a PAI tool. The type of research used is library research, which is the data obtained from books, journals, and articles related to using social media as a learning aid. The data sources obtained were then analyzed using a descriptive approach to obtain information about the use of social media, which can increase the effectiveness of PAI learning in the digital era, things that influence the use of social media, and the impact of using social media as a learning aid. The results of this research show that the use of social media as a means of learning PAI in this digital era is considered very effective and relevant; this is because learning that uses social media has a positive impact in the form of enthusiasm and good responses from students during the learning process. The level of effectiveness can be determined through flexibility of time and place, ease of access, the amount of material and content available on social media, and so on.